2018
DOI: 10.2340/16501977-2493
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in adults with cerebral palsy: A three-year follow-up study

Abstract: People with cerebral palsy are often tired and may complain about fatigue. In this study we describe the development of fatigue over a mean period of 3 years. We found that fatigue is more or less stable over time on a group level. On an individual level there can be important changes, both increases and decreases in fatigue-related symptoms. We did not find any known risk factors for fatigue (for example body mass index, age) to be predictive of change in fatigue over time. We learned that adults with CP, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…As children with CP constantly feel tired, they may perceive a feeling of tiredness as normal and not report it (Schwartz, 2010). One reviewer stated that children with CP who experience fatigue are likely to experience fatigue that does not diminish over time (Lansink et al, 2018). In the present study we obtained further evidence for fatigue management, supporting those prior studies that reported that the fatigue process is probably a complex interaction with decreased motor performance.…”
Section: Discussionmentioning
confidence: 99%
“…As children with CP constantly feel tired, they may perceive a feeling of tiredness as normal and not report it (Schwartz, 2010). One reviewer stated that children with CP who experience fatigue are likely to experience fatigue that does not diminish over time (Lansink et al, 2018). In the present study we obtained further evidence for fatigue management, supporting those prior studies that reported that the fatigue process is probably a complex interaction with decreased motor performance.…”
Section: Discussionmentioning
confidence: 99%
“…Ambulatory adults with CP with complaints of fatigue during daily activities such as walking or cycling, complaints of reduced walking distance or speed, and those with limited ability to perform intensive physical activities were eligible for this cross-sectional multicentre study. Other criteria for participation included: (1) diagnosed with spastic CP according to the Surveillance of Cerebral Palsy in Europe; 15 (2) 16 to 60 years of age; (3) classified in Gross Motor Function Classification System (GMFCS) -Expanded and Revised levels I to III (able to walk with or without assistive devices); 16 (4) no contra-indication for maximal exercise; (5) no severe communication or understanding problems that impede proper measurement performance; and (6) no history of botulinum neurotoxin A injections and/ or serial casting in the past 3 months or surgery in the past 6 months. The study was approved by the Medical Ethical Committee of the University Medical Centre Utrecht, Utrecht (the Netherlands) and the Erasmus MC, University Medical Center, Rotterdam (the Netherlands), and participants signed informed consent before participation.…”
Section: Participantsmentioning
confidence: 99%
“…It has been estimated that up to 40% of adolescents and adults with CP experience fatigue 1–4 . Together with pain and joint deformities, fatigue is one of the most important impairments in people with CP and seems to emerge in adulthood and worsen over time 5 . Furthermore, fatigue is known to impact quality of life and daily activities 1–4 …”
mentioning
confidence: 99%
“…7 Fatigue is commonly assessed using rating scales and there are many self-reporting scales for different aspects of fatigue and for different diseases. [26][27][28][29] However, to the best of our knowledge, there is only one scale designed for use by individuals with CP: the Fatigue Impact and Severity Self-Assessment (FISSA) 26,30 , and its focus is on 'physical tiredness, muscle soreness, exhaustion of your muscles and body, or any related feelings' (p. 6) 26 , not explicitly on mental fatigue. Researchers have stated that there is a need for greater knowledge about how fatigue is manifested in individuals with CP 7,11,26,31 , and studies have underlined the need to detect mental fatigue 7,32 and to find appropriate interventions to ensure a balance between activity and rest 33 in individuals with CP.…”
Section: Introductionmentioning
confidence: 99%